PERANCANGAN DE-MILITARISED ZONE (DMZ) BERBASIS INTRUSION DETECTION SYSTEM (IDS) PADA INFRASTRUKTUR JARINGAN KOMPUTER PEMERINTAH DAERAH KOTA SUKABUMI - Dadan Rahmat; Irman Suherman; Zahara Muharraran; Aulia Khotimah Husna (Universitas Majalengka, 2024)
De-Militarized Zone (DMZ) is a mechanism to protect the internal system from attacks by hackers or other parties who want to enter the system without access rights. The internal system is a confidential information system, the DMZ consists of all open ports that can be seen by outside parties so that hackers attack to crack the server that has the DMZ, so the hacker can only access hosts located in the DMZ. This is done so that internet users who can access the server cannot easily access and reach users on the local network. Within a network, hosts are most vulnerable to attacks that provide services to users outside. As computer networks develop in the Sukabumi City Regional Government, implementing a computer network security system model should be the main focus considering that there are many public services with high security risks and also the absence of a security system that can minimize data or application security risks on computer networks.